PRMT1 alleviates isoprenaline-induced myocardial hypertrophy by methylating SRSF1 - Yan Zi; Zhao Wenhui; Zhao Naixin; Liu Yufeng; Yang Bowen; Wang Li; Liu Jingyi; Wang Deping; Wang Jin; Jiao Xiangying; Cao Jimin; Li Jianguo (Acta Biochimica et Biophysica Sinica)
Myocardial hypertrophy (MH) is an important factor contributing to severe cardiovascular disease. Previous studies have demonstrated that specific deletion of the protein arginine methyltransferase 1 (PRMT1) leads to MH, but the exact mechanism remains unclear. Serine/arginine-rich splicing factor 1 (SRSF1) affects the development and progression of cardiovascular disease by selectively splicing downstream signaling proteins. The present study is designed to determine whether PRMT1 is involved in MH by regulating SRSF1 and, if so, to explore the underlying mechanisms. Adult male mice and H9C2 cardiomyocytes are treated with isoprenaline (ISO) to establish MH models. The expression levels of PRMT1 are significantly decreased in the ISO-induced MH models, and inhibiting PRMT1 worsens MH, whereas overexpression of PRMT1 ameliorates MH. SRSF1 serves as the downstream target of PRMT1, and its expression is markedly elevated in MH. Moreover, SRSF1 increases the mRNA expressions of CaMKIIδ A and CaMKIIδ B, decreases the mRNA expression of CaMKIIδ C by altering the selective splicing of CaMKIIδ, and further participates in MH. In addition, there is an interaction between PRMT1 and SRSF1, whereby PRMT1 reduces the phosphorylation level of SRSF1 via methylation, thus further altering its functional activity and eventually improving MH. Our present study demonstrates that PRMT1 relieves MH by methylating SRSF1, which is expected to provide a new theoretical basis for the pathogenic mechanism of MH and potential drug targets for reducing MH and associated cardiovascular disease.